Ferrari’s method for solving a quartic equation

$$x^4-15x^2-10x+ 24 = 0$$

begins by writing:$$x^4= 15x^2+ 10x-24$$and then adding a term of the form:$$-2bx^2+b^2$$to both sides.

(a) Explain why this is good idea and what it accomplishes.

(b) Use $b= 7$ to find the two quadratic equations that yield the solutions.


I have

$$\begin{align*}x^4-2bx^2+b^2&=15x^2+ 10x-24-2bx^2+b^2\\\\ &=(15-2b)x^2+ 10x+(b^2-24) \end{align*}$$

I then notice that $$x^4-2bx^2+b^2=(x^2-b)^2$$

so we get

$$(x^2-b)^2=(15-2b)x^2+ 10x+(b^2-24)$$

Pluggin in $b=7$ I get

$$(x^2-7)^2=x^2+ 10x+25$$

but I fail to see why this helps with regards to solving for $x$.

Any hints to lean me in the direction would be much appreciated.

  • 4
    $\begingroup$ $x^2 + 10x + 25 = (x+5)^2$? $\endgroup$ – Anton Grudkin Mar 15 '18 at 2:03
  • $\begingroup$ I don't know how I didn't notice that... $\endgroup$ – Remy Mar 15 '18 at 2:05

$$(x^2-7)^2=x^2+ 10x+25\implies (x^2-7)^2-(x+5)^2=0$$


Now solve each quadratic equation for $ x$


$$(x^2-7)^2 = (x+5)^2$$



  • $\begingroup$ I want for newcomer explain @Mohammad's and Siong's move : Let $A=a_1+a_2$ and $B=b_1+b_2$ $$$$ \begin{align} A^2-B^2=0\\ (A-B)(A+B)=0 \\ (a_1+a_2-(b_1+b_2))(a_1+a_2+b_1+b_2)=0 \\ (a_1+a_2-b_1-b_2)(a_1+a_2+b_1+b_2)=0 \end{align} $\endgroup$ – Krzysztof Myśliwiec Sep 20 '18 at 18:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.